Blood Coagulation Activation in Cancer: Challenges for Cancer Treatment - Zacharski, L. R.; Costantini, V. (Hämostaseologie, 1995)
It has been known for over a century that blood coagulation and fibrinolysis pathways are activated systemically in patients with malignancy. Recent studies have revealed evidence for two distinct pathways of interaction between tumor cells and the host coagulation mechanism that include production of either initiators of thrombin formation or expression of plasminogen activators by the tumor cells in situ within intact tumor tissue. Studies in specific in vitro and animal models of malignancy have implicated either tumor cell procoagulants or urokinase in mechanisms of tumor cell proliferation, invasion, and metastasis. We have formulated a classification of human tumor types based on detection of components of either of these pathways in situ. Type I tumors are those in which the tumor cells are associated with an intact coagulation pathway that leads to thrombin formation at the tumor periphery but in which the tumor cells lack urokinase. Type II tumors are those in which the tumor cells express urokinase but lack an associated coagulation pathway leading to thrombin formation. Type III tumors are those that express neither of these pathways, or exhibit some other pattern of interaction. Evidence suggests that anticoagulant therapy is capable of ameliorating the clinical course of a procoagulant tumor type namely, small cell carcinoma of the lung. This approach may be effective in other type I tumors. Clinical trials of agents capable of inhibiting urokinase-initiated proteolysis are required to clarify cause/effect relationships in urokinase-expressing tumors. Exploration of the coagulation-cancer interaction holds considerable promise for imaginative new approaches to cancer treatment that are not only relatively nontoxic and low cost, but also effective because they may interrupt fundamental mechanisms of malignant growth control.
Keywords: Blood coagulation; cancer; thrombin; urokinase